1990
DOI: 10.1016/0378-3782(90)90123-z
|View full text |Cite
|
Sign up to set email alerts
|

Skin blood flow changes, measured by laser Doppler flowmetry, in the first week after birth

Abstract: SummaryChanges in forehead skin blood flow were determined in 17 healthy, term newborns, using a fiberless diode laser Doppler flow meter (Diodopp). Measurements were carried out three times on each infant, at postnatal ages of 16.8 f 7.4 h, 58.9 f 6.2 h and 121.5 -C 14.2 h (mean + SD.), respectively. Skin blood flow, respiration, heart rate and skin temperature were recorded simultaneously, while the newborns were asleep. During the recordings, the behavioural state of the newborns was observed and environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Reports of temporal changes in neonatal peripheral cutaneous blood flow are similarly conflicting (22,24). Although microvascular blood flow has been reported to remain unchanged over the first 24 h of life (13), other authors have described significant falls between days 1 and 7 (12,22). The current data demonstrates that in term neonates born after preeclamptic pregnancy, female infants exhibit similar baseline microvascular blood flow at 6 h of age to females of normotensive mothers followed by significantly greater microvascular blood flow at 24 and 72 h. Conversely, male infants do not demonstrate a temporal change in blood flow in the presence of preeclampsia but were significantly more vasodilated than males of normotensive mothers at 6 h of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of temporal changes in neonatal peripheral cutaneous blood flow are similarly conflicting (22,24). Although microvascular blood flow has been reported to remain unchanged over the first 24 h of life (13), other authors have described significant falls between days 1 and 7 (12,22). The current data demonstrates that in term neonates born after preeclamptic pregnancy, female infants exhibit similar baseline microvascular blood flow at 6 h of age to females of normotensive mothers followed by significantly greater microvascular blood flow at 24 and 72 h. Conversely, male infants do not demonstrate a temporal change in blood flow in the presence of preeclampsia but were significantly more vasodilated than males of normotensive mothers at 6 h of age.…”
Section: Resultsmentioning
confidence: 99%
“…The microcirculation of neonate is subject to considerable changes in the first days of extrauterine life (12) and is altered in response to mode of delivery (13), hypoxia (14), and ischemia (15). We have recently demonstrated that infants born prematurely exhibit sex-specific differences in microvascular blood flow and vasodilatory capacity (16).…”
mentioning
confidence: 99%
“…However, at this time, dramatic functional and structural changes are still occurring in the macrocirculation and microcirculation as adaptation to the extrauterine environment takes place (36). Indeed, previous studies using laser Doppler flowmetry have documented marked changes in skin blood flow during the first 5 days of life (37). At the age of 3 months, the transient changes in blood volume (38) and metabolism that follow parturition have largely stabilized, and the maturation of biological rhythms of the cardiovascular and thermoregulatory system would have occurred (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the microcirculation of the skin is subject to considerable changes in the first few days of extrauterine life. 15 An extensive capillary network in the newborn's skin forms in the first weeks after birth first in a disorderly manner, and then, between 14 and 17 weeks after birth, the length and variability of the diameter of the capillaries increase. 16,17 This is consistent with the recent report by Top et al, 18 who examined the capillary microcirculation in the buccal mucosa in term neonates at 0 to 7 days, 8 to 28 days, 1 to 6 months, and at 3 years using orthogonal polarized spectroscopy imaging and found higher basal capillary density in infants Ͻ1 week old compared with older children, confirming that basal capillary density decreases progressively after the first week of life.…”
Section: Discussionmentioning
confidence: 99%